Pediatric pulmonary actinomycosis: A misdiagnosed case report - Yilin, Zhao; Xinyi, Liu; Longwei, Sun; Hongwu, Zeng (Frontiers in Pediatrics, 2022)
Background: Pulmonary actinomycosis is an uncommon kind of bacterial illness caused by actinomycetes, involving the chest wall is extraordinarily rare. Due to non-specific clinical signs and perplexing radiological characteristics, this kind of pulmonary actinomycosis is frequently misinterpreted as a malignant tumor or lung abscess. Case presentation: An 11-year-old child appeared with a palpable lump on his left chest and periodic chest discomfort. An irregular soft-tissue mass in the left upper zone with bony destruction was first identified as a malignant small round cell tumor (MSRCT) named Askin tumor on post-contrast CT and MRI. However, pathological biopsy of the pulmonary lesion through the chest wall revealed actinomycosis. Conclusion: Pulmonary actinomycosis is an uncommon bacterial illness that has a variety of clinical manifestations, particularly in youngsters. Radiological imaging of a lung mass with nearby rib "lace-like" bone deterioration is strongly indicative of pulmonary actinomycosis, according to our case report. The diagnosis can be confirmed by microbiological culture, pathological biopsies, or second-generation sequencing of alveolar lavage fluid.